Pengaruh Tingkat Pemanfaatan Media Komunikasi Inovasi Baru (Cyber Extension) dalam Mewujudkan Keberdayaan Petani Kopi di Kabupaten Lampung Barat - Mariman, Mariman; Gultom, Dame Trully; Ibnu, Muhammad; Sayekti, Wuryaningsih Dwi; Yanfika, Helvi (Suluh Pembangunan : Journal of Extension and Development, 2024)
The importance of utilizing information technology, including Cyber Extension, in West Lampung is becoming increasingly apparent along with the development of globalization and digital transformation. The purpose of this study was to determine the level of utilization of cyber extension, determine the level of empowerment of coffee farmers and analyze the effect of the level of utilization of cyber extension on the empowerment of coffee farmers. This research was conducted in West Lampung Regency using a quantitative descriptive approach with a sample size of 125 respondents. The level of utilization of cyber extension by coffee farmers in West Lampung Regency is generally classified in the high enough category, meaning that farmers have used and utilized digital technology to manage information related to coffee farming, besides that the level of empowerment of coffee farmers is low, this is due to the lack of ability of farmers in managing results and determining coffee prices. Based on the results of the analysis, it is known that the level of utilization of cyber extension has a significant influence on the empowerment of coffee farmers in West Lampung.